Pemanfaatan Limbah Pabrik Teh (Camelis Sinensis) sebagai Pupuk Kompos (Studi Kasus UMKM Pembuatan Minuman Teh) - Priyanto, Ibay Edi; Supriyanto, Supriyanto; Adriansyah, Putri Nabila Adinda (DPPM UNIVERSITAS PELITA BANGSA, 2022)
Tea solid waste comes from the remaining beverage production that has gone through two processing processes, then the resulting tea waste is processed into compost through the stages of waste separation, weighing the waste, drying the waste, making a solution between water and em4, and composting. This research aims to understand the compost making process, analyze the elements contained in the compost, analyze the quality of the compost according to SNI 19-7030-2004, and analyze the ideal dosage for plant growth. Composting was carried out for 27 days. Before the compost was used, laboratory tests were carried out between the tea waste and the tea waste compost and the compost results were compared with the SNI 19-7030-2004 Compost Quality Standard. The compost that has gone through the laboratory tests was applied to mustard plants (camelis sinensis) by giving different doses in each polybag starting from the treatment dose of 0%, 2.5%, 5%, 7.5%, 10%, 12.5% ​​and 15%. With the weight parameter of mustard greens (camelis sinensis), the weight determination technique is to remove the plants from each polybag and then weigh them within seven days in seven scales. The results of laboratory tests of 9 SNI 19-7030-2004 Compost parameters only 3 meet the standards, so it is concluded that the composting process takes 27 days, the compost is not fully mature. The ideal plant observation application on the growth of mustard plants (camelis sinensis) in this study is at a dose of 12.5% ​​​​with the highest mustard plant weight (camelis sinensis) of 12.1 g with an average weekly weight of 8.6 g.